Microbial biomarkers to identify areas of wetland sediments affected by massive fish farming - Lian, Yanqing; Zhen, Lisha; Fang, Yan; Li, Hao; Li, Xiaona; Li, Yang; Xu, Xinhan (Frontiers in Environmental Science, 2022)
Massive fish farming for more than two decades, combined with external sources of pollution, deteriorated the quality of water and sediment and damaged the ecosystem in the Honghu Lake. Although water quality has been improving, great challenges remain in restoring the healthy function of ecosystems for self-mitigation. With concerns on contaminants in the sediment that might be the secondary source of pollution, water and sediment samples were collected systematically across the wetland. With the 16s rDNA gene sequence and multiple statistical analyses this study was able identify locations where sediments were mostly impacted by non-point source pollution from its surrounding agricultural areas and fish farming inside the lake. The clustering analysis identified the two distinct clusters coincide with areas with and without fish farming. The LEfSe algorithm successfully distinguished the differentially abundant biomarkers between the two clusters. With the GIS techniques this study localized hazardous pathogenic bacteria such as Rokubacteria, Elusimicrobia, and Fusobacteria in sediments across the lake. This study proved the comprehensive biodiversity analysis combined with the spatial analysis could make the microbial information serve well as biomarkers and indicators for environmental and ecosystem restoration.